2015
DOI: 10.3892/etm.2015.2667
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of type II collagen-induced arthritis in Wistar rats

Abstract: Abstract. The aim of the present study was to determine a more specific, efficient and simple method for the induction of collagen-induced arthritis (CIA) in rats. Different strains of rats were injected at the base of the tail with bovine type II collagen (CII) emulsified in incomplete Freund's adjuvant (IFA). The onset and severity of arthritis were evaluated by clinical assessment. The established CIA model was analyzed using a comprehensive examination of clinical, hematological, histological and radiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 19 publications
0
32
0
4
Order By: Relevance
“…Previous study suggested that female Wistar rats were greatly susceptible to CIA and had low variability in clinical signs. 9 Therefore, the CIA model was induced in female Wistar rats in this study.…”
Section: Induction Of Cia In Ratsmentioning
confidence: 99%
“…Previous study suggested that female Wistar rats were greatly susceptible to CIA and had low variability in clinical signs. 9 Therefore, the CIA model was induced in female Wistar rats in this study.…”
Section: Induction Of Cia In Ratsmentioning
confidence: 99%
“…Paw arthritic signs characterized by edema and erythema were inspected daily following the CII/IFA injection. To evaluate the incidence and severity of arthritis, lesions on all four paws of each rat were graded by using an arthritic scoring system (13). Lesions were graded using a scale from 0 to 4 according to the extent of edema and erythema of the periarticular tissues; 16 was the potential maximum of the combined arthritic scores per animal.…”
Section: Introductionmentioning
confidence: 99%
“…Até o presente, os processos inflamatórios articulares foram bem caracterizados em modelos experimentais que mimetizam a AR humana. O desenvolvimento da AR vem sido bem descrito em uma ampla variedade de modelos animais com utilização de diversos estímulos, como colágeno, adjuvante de Freund, proteoglicanos, pristanos, avridinas, antígenos entre outros, que são capazes de simular/desencadear respostas celulares, bioquímicas, imunológicas e alterações histológicas que mimetizam em grande parte as condições patológicas da AR humana (DURIE, FAVA e NOELLE, 1994;BRAND et al, 1996;ZHANG et al, 2013;PINTO et al, 2015;SONG et al, 2015;BESSIS et al, 2017).…”
Section: Ar E Modelos Experimentaisunclassified
“…Neste contexto, o modelo experimental de artrite induzida por colágeno (AIC) apresenta características fisiopatológicas semelhantes à AR humana, além de ser amplamente utilizado para ilustrar os mecanismos patológicos relevantes na AR humana e para identificar potenciais agentes terapêuticos (DURIE, FAVA e NOELLE, 1994SONG et al, 2015;BESSIS et al, 2017). Em ambos tipos de artrite, células do sistema imune e dos tecidos sinoviais produzem uma série de citocinas inflamatórias e outros mediadores solúveis em uma cascata inflamatória.…”
Section: Ar E Modelos Experimentaisunclassified
See 1 more Smart Citation